Self-Management Ability Questionnaire Validation in Portuguese Adults With Periodontitis - Eloïse Gobin; Catarina Izidoro; Patrícia Lyra; Mariana Morgado; Ricardo Castro Alves; José João Mendes; João Botelho; Vanessa Machado (Elsevier, 2023)
Objectives: We aimed to test the psychometric validity of the adapted and translated Self-Management Ability Questionnaire-Short Form (SMAQ-12) to Portuguese. Methods: The translation and adaptation of the SMAQ-12 followed international guidelines. We included 280 participants with chronic periodontitis from the Department of Periodontology of the Egas Moniz Dental Clinic. Participants completed the Portuguese version of the SMAQ-12 (SMAQ-12-PT), a 12-item scale with 3 conceptual domains (Role Management, Medical Management, and Emotional Management). The validity of the content, its construct and internal consistency, as well as test-retest reliability were used to estimate psychometric properties. Results: The SMAQ-12-PT showed an interclass correlation coefficient value of 0.90, with a 95% confidence interval (0.79-0.95; P < .001) and high reliability (Cronbach alpha coefficient ranging between 0.78 and 0.94). Confirmatory factor analysis revealed adequate model fit, with comparative fit index of 0.853, goodness-of-fit of 0.947, and a 0.052 value of root mean squared error of approximation. Conclusions: The SMAQ-12-PT was found to be a valid and reliable instrument in the Portuguese population. Disease management representation for the specialty of periodontology and its impact on periodontal schedules and practices should be evaluated in future studies.